Respuesta :
____________________________________________________
Answer:
7k
____________________________________________________
Step-by-step explanation:
We are trying to combine like terms with the expression: -k - ( - 8k)
We are pretty much solving it.
Solve:
-k - ( - 8k)
The "- ( -" turns into a plus sign.
So it would look like:
-k - -8k or -k + 8k
Now, you would finish solving
-k + 8k = 7k
____________________________________________________
Answer:
7k
Step-by-step explanation:
note that - (- k) = + k
Given
- k - (- k) = - k + 8k = 7k